The bat–bird–bug battle: daily flight activity of insects and their predators over a rice field revealed by high-resolution Scheimpflug Lidar. Issue 4 (4th April 2018) - Malmqvist, Elin; Jansson, Samuel; Zhu, Shiming; Li, Wansha; Svanberg, Katarina; Svanberg, Sune; Rydell, Jens; Song, Ziwei; Bood, Joakim; Brydegaard, Mikkel; Åkesson, Susanne
Abstract : We present the results of, to our knowledge, the first Lidar study applied to continuous and simultaneous monitoring of aerial insects, bats and birds. It illustrates how common patterns of flight activity, e.g. insect swarming around twilight, depend on predation risk and other constraints acting on the faunal components. Flight activity was monitored over a rice field in China during one week in July 2016, using a high-resolution Scheimpflug Lidar system. The monitored Lidar transect was about 520 m long and covered approximately 2.5 m 3 . The observed biomass spectrum was bimodal, and targets were separated into insects and vertebrates in a categorization supported by visual observations. Peak flight activity occurred at dusk and dawn, with a 37 min time difference between the bat and insect peaks. Hence, bats started to feed in declining insect activity after dusk and stopped before the rise in activity before dawn. A similar time difference between insects and birds may have occurred, but it was not obvious, perhaps because birds were relatively scarce. Our observations are consistent with the hypothesis that flight activity of bats is constrained by predation in bright light, and that crepuscular insects exploit this constraint by swarming near to sunset/sunrise to minimize predation from bats.